COMPLEX ANALYSIS OF COMPANY BANKRUPTCY FORECASTING: THEORETICAL INSIGHT - Mackevičius, Jonas; Šneidere, Ruta; Tamulevičienė, Daiva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In modern conditions for dynamic and competitive businesses, more and more companies face financial problems and eventually go bankrupt. A noteworthy trend: not only new companies that have not yet managed to establish themselves in the market go bankrupt but also large companies operating for years and maintaining good traditions. Bankruptcies of companies cause many problems not only for the companies themselves but also for the state and many members of society. Thus, it is crucial to evaluate the financial state of a company and its activity results as accurately and early as possible when forecasting the possibility of a bankruptcy. The paper recommends a complex analysis methodology for forecasting company bankruptcies. It consists of the following elements: 1) study of the external and internal environments; 2) evaluation of changes of absolute financial indicators;3) calculation and evaluation of financial ratios; 4) application of bankruptcy prediction models; 5) research of bankruptcy causes and 6) application of operational and prospective measures to avoid bankruptcy. By carrying out a thorough analysis of each of these elements, it is possible to obtain detailed and objective information about the company's financial status, activity results and cash flows as early as possible and anticipate the possibilities of the company's business continuity.